PENGARUH GROWTH OPPORTUNITY, LEVERAGE, FIRM SIZE, NET WORKING CAPITAL AND INVESTMENT OPPORTUNITY SET TERHADAP CASH HOLDING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Atik Rohmah Maghfiroh; Nur Diana; Junaidi Junaidi (Universitas Islam Malang, 2022)
The purpose of this study is to look at the effect of growth potential, leverage, firm size, net working capital, and investment opportunity set on cash holding in manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2018 and 2020. The purposive sampling method was utilized to gather 61 samples of businesses. Multiple linear regression analysis is applied to analyze the data in this study. SPSS 20.0 for Windows is used in this data analysis technique. The findings show that: 1) growth opportunity, firm size, net working capital, and investment opportunity set all have a simultaneous effect on cash holding, 2) growth opportunity, leverage, and networking capital both have a partial effect on cash holding and 3) firm size and investment opportunity set all have no partial effect on cash holding.Keywords: Cash Holding, Growth Opportunity, Leverage, Firm Size, Net Working Capital, Investment Opportunity Set